1994
DOI: 10.1002/jbm.820280308
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite coatings on Ti produced by hot isostatic pressing

Abstract: Plasma spraying is a technique currently used in the production of HA-coated titanium implants. These coatings have been shown to be porous; they dissolve and have a weak bond to the substrate. The long-term interface strength has been questioned in particular. The aim of the present work was to produce HA coatings without the shortcomings of those produced by plasma spraying. Hot isostatic pressing (HIP) at 850 degrees C and 1000 bar with no holding time was applied for this purpose. Initially, the HA powder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 9 publications
1
45
0
1
Order By: Relevance
“…Some of the coating methods of the first approach include electrophoretic deposition (Ducheyne et al 1990), plasma spraying (De Groot et al 1990;Thull & Grant 2001), radio frequency or ionic ray sputtering (Cook et al 1988), laser ablation (Clèries 1999;Serra et al 2001) or hot isostatic pressure (Hero et al 1994). None of these methods produce covalent links with the substrate, and the majority are not cost-effective.…”
Section: Metalsmentioning
confidence: 99%
“…Some of the coating methods of the first approach include electrophoretic deposition (Ducheyne et al 1990), plasma spraying (De Groot et al 1990;Thull & Grant 2001), radio frequency or ionic ray sputtering (Cook et al 1988), laser ablation (Clèries 1999;Serra et al 2001) or hot isostatic pressure (Hero et al 1994). None of these methods produce covalent links with the substrate, and the majority are not cost-effective.…”
Section: Metalsmentioning
confidence: 99%
“…Numerous efforts have been made to enhance the surface roughness of conventional titanium/alloy implants, including electrophoretic deposition, 2 sputtering 3 or hot pressing. 4 It is found that the surface roughness fabricated by these methods is limited to the micrometer scale, but the samples are featureless at the nanoscale. 5 Recently, it has been reported that surfaces with nano features, either disordered 6,7 or ordered (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, several surface modifications have been employed which alter one or more of these properties in an attempt to achieve more favorable bone responses. Some techniques such as plasma spraying [2], laser deposition [3], ion beam dynamic mixing [4], ion beam deposition [5], magnetron sputtering [6], hot isostatic pressing [7], electrophoretic deposition [8], sol-gel [9], ion implantation [10], NaOH treatment [11] and electrochemical methods [12], have been employed to coat hydroxyapatite (HA) or other calcium phosphate on the surface of Ti. However, each method has some disadvantages.…”
Section: Introductionmentioning
confidence: 99%